Analisis Keterampilan Berpikir Kritis Peserta Didik Melalui Model Inkuiri Terbimbing Pada Materi Laju Reaksi - Ramadhanti, Arviana; Agustini, Rudiana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This research aimed to analyse students’ critical thinking skills on reaction rate material. The learning process was done online using the guided inquiry model. This research applied quantitative descriptive method designed with one group pretest-posttest pattern. Subjects involved in this research was 32 students of class XI MIPA 1 SMA Negeri 1 Taman. Research data was collected from observation and test results through observation sheets of learning model workability and critical thinking question sheets. The data analysis technique used in this research is quantitative analysis with statistical test. The result shows that student’s critical thinking skills increased which seen from n-gain score as follows: interpretation indicator as of 0.74; inference as of 0.76; and explanatory as of 0.86 with high category and analysis indicator as of 0.63 which was middle category. The result of paired sample t-test examination showed the number of sig. (2-tailed) 0.000 that stated whenever found big and significant difference between posttest and pretest scores which indicated the application of guided inquiry model during learning took effect on increasing students’ critical thinking skills.